PENGARUH PEMUPUKAN FOSFAT TERHADAP PRODUKTIVITAS TANAH INCEPTISOL DAN ULTISOL - A. Kasno; D. Setyorini; E. Tuberkih (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2006)
Phosphorus is one of macro nutrient which becomes limiting factor for plant growth on the upland. Available soil P is low because fixations by Al, Fe, and Mn oxide make it unavailable for plant. The objective of this research is to study the effect of phosphorus fertilizer on soil productivity, growth and corn production. The research was conducted on Inceptisols in Cibatok, Cibungbulang, Bogor and Ultisols in Jagang, South Abung, North Lampung on dry season 2004. The experiment used randomized complete block design, with three replications. The doses of P fertilizer to try were: 0, 20, 40, 60 and 80 kg P ha-1. Sources P fertilizer to use were TSP Anjing Laut and SP- 36 (40 kg P ha-1). The results of this research show that P fertilizer significantly increase plant height, and weight of production. The optimum dose of P fertilizer for corn on Inceptisols and Ultisols ranges from 20 to 40 kg ha-1. The use of P from the sources which have similar solubility in water have the same effect on soil productivity.